2018
DOI: 10.1016/j.ijdevneu.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

mRNA expression of transient receptor potential melastatin (TRPM) channels 2 and 7 in perinatal brain development

Abstract: TRPM7 and TRPM2 are non-specific cation channels of the Transient Receptor Potential channel superfamily. Each channel has gained attention for their potential to mediate oxidative and anoxic cell death (Rama and García, 2016; Nazıroğlu, 2011a; Abiria et al., 2017; Sun, 2017), however their physiological expression and roles in the developing brain remain poorly defined. We employed real-time reverse transcription PCR to examine mRNA expression of TRPM7 and TRPM2 in the developing rat brain and brain-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 109 publications
0
4
0
Order By: Relevance
“…In addition, TRPM2 channels can be acutely inhibited at delayed time points after CA/CPR by applying tatM2NX onto acute hippocampal slices which reverses LTP deficits in adults, indicating that TRPM2 channels impair synaptic plasticity through persistent activation [ 10 ]. Together, our data highlight two important hypotheses: (a) although TRPM2 channels are expressed at similar levels in juvenile and adults ( Figure 1 and see [ 39 ]), the role of this channel in cell death is age dependent, and (b) TRPM2 channel activation impairs synaptic plasticity both acutely and chronically and may be targeted to restore cognitive function after global cerebral ischemia, despite a lack of neuroprotection in the young brain. We suggest that disparate pathways exist for cell death and synaptic impairment by TRPM2.…”
Section: Discussionmentioning
confidence: 52%
“…In addition, TRPM2 channels can be acutely inhibited at delayed time points after CA/CPR by applying tatM2NX onto acute hippocampal slices which reverses LTP deficits in adults, indicating that TRPM2 channels impair synaptic plasticity through persistent activation [ 10 ]. Together, our data highlight two important hypotheses: (a) although TRPM2 channels are expressed at similar levels in juvenile and adults ( Figure 1 and see [ 39 ]), the role of this channel in cell death is age dependent, and (b) TRPM2 channel activation impairs synaptic plasticity both acutely and chronically and may be targeted to restore cognitive function after global cerebral ischemia, despite a lack of neuroprotection in the young brain. We suggest that disparate pathways exist for cell death and synaptic impairment by TRPM2.…”
Section: Discussionmentioning
confidence: 52%
“…It has been shown that the TRPM2 is widely expressed in the human and as well as rat striatum [53,54]. From our ndings, it is now established that both inhibitors exhibit the neuroprotective effects in the MPTP-induced PD animals.…”
Section: Discussionmentioning
confidence: 74%
“…TRPM2 resides not only in neurons, but also astrocytes or microglial cells, which play a role in cognitive functions [91][92][93][94]. The mRNA expression profile in microglia of TRPM2 in the hypothalamus and striatum of the developing rat brain has been shown to be paralleled with the perinatal expression timeline for microglial infiltration and maturation [95]. TRPM2 has been shown to be involved in embryonic neurogenesis [96].…”
Section: Discussionmentioning
confidence: 99%